Evaluation of Distillers Dried Grains with Solubles in Combination with Glycerin in Broiler Diets - Min, Y.N.; Liu, F.Z.; Wang, Z.; Coto, C.; Cerrate, S.; Costa, F.P.; Yan, F.; Waldroup, P.W. (International Journal of Poultry Science, 2008)
An experiment was conducted to evaluate the use of distillers dried grains with solubles (DDGS) combined with glycerin in broiler diets. In a 3x2 factorial arrangement, 600 one-day-old commercial strain Cobb 500 broilers were randomly assigned to experimental diets with 0, 15 and 30% DDGS of known composition; within each level of DDGS the diets contained 0 or 5% glycerin, respectively, from 0-42 days of age. Diets were formulated to meet digestible amino acid requirements and were fed in pelleted form. Each dietary treatment was replicated 4 times. Body weight gain and feed consumption were measured and carcass characteristics were evaluated at 42 days of age. Inclusion of 30% DDGS had no adverse effect on body weight of chicks; however birds fed diets with 30% DDGS had greater feed intake and poorer feed conversion than birds fed the control diet at most age periods. This was highly correlated to the reduced pellet quality of diets containing the high levels of DDGS. Birds fed diets with 30% DDGS also had significantly reduced dressing percentage compared to birds fed the control diet with no DDGS. However, there was no adverse effect on breast meat yield related to the higher levels of DDGS inclusion. Addition of 5% glycerin from biodiesel production to the diets had no significant effect on body weight, feed intake, or feed conversion. There was no significant effect of the addition of glycerin on dressing percentage or yield of various carcass parts. With one minor exception, there was no significant interaction between addition of glycerin and level of DDGS in the diet, even though pellet quality declined when glycerin was added to the diets. Overall, the results of this study demonstrates that 15% DDGS of known nutritional quality can be utilized in diets for growing broilers with no adverse effects provided diets are formulated on a digestible amino acid basis and meet the nutritional requirements of the broiler. Higher levels may be tolerated but there may be a loss in feed conversion unless pellet quality can be improved. A loss in dressing percentage at higher levels of DDGS has been consistently noted in this and previous studies. Incorporation of 5% glycerin from biodiesel production as a source of energy appears satisfactory.